Exploring Talent Management Potential in Digital-Savvy SMEs: A Case Study from Yogyakarta, Jakarta, and Bandung - Monica Yanuardani (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
Digitalization offers a new direction in creating opportunities for business to support national economic growth. Indonesia, as the rising star in Southeast Asia emerging market, shows a promising employment prospect along with the increasing growth of digital savvy Small-Medium Enterprises (SMEs). There is a growing need for SMEs to understand Talent Management (TM) better and optimize the digital economy potential in Indonesia. Nonetheless, TM in SMEs is still under research in Indonesia since most of the Human Resource Management studies were conducted in well-established large enterprises. Accordingly, this study aims to explore TM, especially in digitalsavvy SMEs that using internet platforms in their business. By using cluster analysis, this study presents the pattern of TM issues: attract, select, develop and retain key talented employees. This exploratory study involved CEOs and managers of digital-savvy SMEs in Jakarta, Bandung, and Yogyakarta. This study also aims to map the awareness of SMEs in harnessing the demographic growth of the young population in Indonesia. In addition, early identification of TM challenges - related to digital-savvy concern - will contribute not only to the SMEs in scaling up their business, but also newly stage entrepreneurs who are commencing their start-ups and attracting new talents. As part of the discussion, this study proposed a perspective that the digital economy will produce the “New Working Life” employment in the nearly future which entails the more flexible time, place, work tasks and social interaction which might answer the geographical challenges of the archipelago in Indonesia.